A "perfect Janus emulsion": Thermodynamic factors. Issue 4 (3rd April 2017) - Kovach, I.; Friberg, S. E.; Koetz, J.
ABSTRACT: The topology and interfacial thermodynamics of "perfect Janus emulsions" are considered, using two cases to illustrate the range of topological features. Initially, the correlation is established between lobe volumes and the location of the contact line, followed by a description of the essential angles involved and finally the requirements for interfacial tensions. GRAPHICAL ABSTRACT: